Maqasid al-shari'ah, maslahah and corporate social responsibility - Dusuki, Asyraf Wajdi; Abdullah, Nurdianawati Irwani (The International Institute of Islamic Thought, 2007)
The doctrine of corporate social responsibility (CSR), which has emerged and developed rapidly as a field of study, is a framework for the role of business in society. It sets standards of behavior to which a company must subscribe in order to impact society in a positive and productive manner while abiding by values that exclude seeking profit at any cost. Despite the many attempts to construe CSR initiatives, it remains open to wide criticism for its inherent problems via-à-vis justification, conceptual clarity, and possible inconsistency. These problems are more acute when it comes to implementing and operationalizing CSR on the ground,especially in a situation that involves trade-offs. This paper offers an instructive understanding of CSR from an Islamic perspective. In particular, the implication of maqasid al-Shari`ah (the Shari`ah’s objectives) and the application of maslahah (the public good) to CSR are discussed in detail to shed light on how Islam’s holistic and dynamic perception of CSR take into consideration reality and ever-changing circumstances. These principles also provide a better framework that managers can use when faced with potential conflicts arising from the diverse expectations and interests of a corporation’s stakeholders.